Copper Mediated Intramolecular vs. Intermolecular Oxygenations: The Spacer makes the Difference!. Issue 5 (15th January 2022) - Petrillo, Alexander; Hoffmann, Alexander; Becker, Jonathan; Herres‐Pawlis, Sonja; Schindler, Siegfried
Abstract: Copper complexes in combination with dioxygen are important as potential catalytic systems for regio‐ and stereoselective aerobic oxygenations of aromatic and aliphatic C−H bonds at ambient temperatures. In that context we herein describe a copper(I) complex with an imine ligand derived from (+)‐camphor and 2‐(2‐aminoethyl)pyridine that forms a bis( μ ‐hydroxido) dicopper complex upon reaction with dioxygen at room temperature. It is detectable by UV‐vis for several hours up to a few days, depending on the solvent and could be structurally characterized. In contrast to previous observations this complex rather oxygenates acetone or thioanisole as external substrates instead of undergoing an intramolecular ligand hydroxylation. Abstract : A copper(I) complex with an imine ligand derived from (+)‐camphor and 2‐(2‐aminoethyl)pyridine formed a bis( μ ‐hydroxido) dicopper complex upon reaction with dioxygen at room temperature. The complex could be structurally characterized and in contrast to previous observations it rather oxygenates acetone or thioanisole as external substrates instead of undergoing an intramolecular ligand hydroxylation.